Epiphytic diatoms on leaf blades of Enhalus acoroides in Cancabato Bay, Leyte, Philippines from March to April 2014 - Alonzo, Coleen O. (Division of Natural Sciences and Mathematics, University of the Philippines Visayas Tacloban College, 2014)
Epiphytic diatoms attach on seagrass blades which serve as their substrata. In return, these diatoms increase the primary productivity of the seagrass community. Sensitivity of these diatoms to environmental factors deemed it as good bioindicators of the marine environment. This is a pioneering study on epiphytic diatoms on seagrass blades, E. acoroides in Cancabato Bay. This study contributes to the growing knowledge of ecology of the epiphytes and their relationship to their E. acoroides hosts especially on the composition of epiphytic diatom genera,, their relative abundance and effect of Supertyphoon Haiyan to their densities. Ten mature E. acoroides blades were sampled from three stations in the bay. Diatoms were scraped from the leaves, identified and quantified. The genera of epiphytic diatoms identified were Amphora, Bacillaria, Cocconeis, Fragilaria, Leptocylindrus, Liicmophora, Navicula, Nitzschia, Rhizosolenia, and Skeletonema. There were no significant differences in dominating secondary and accompanying genera within stations of the bay. The most abundant genera in the bay were Cocconeis sp. (27%) and Nitzschia sp (23%). The mean total density of epiphytic diatoms on E. acoroides in the bay was 36 +/- 8.98 cells/cm squared.